Efficacy of prolonged exposure therapy for a patient with late-onset PTSD affected by evacuation due to the Fukushima nuclear power plant accident. Issue 12 (29th December 2019) - Hori, Arinobu; Takebayashi, Yoshitake; Tsubokura, Masaharu; Kim, Yoshiharu
Abstract : Trauma-focused cognitive–behavioural therapy (TF-CBT), such as prolonged exposure therapy, is a first-line treatment for post-traumatic stress disorder (PTSD). However, adapting TF-CBT as an intervention in situations with limited resources, such as in disaster settings, is problematic. This case report concerns a Japanese man in his 30s who was diagnosed with late-onset PTSD 5 years after the 2011 Great East Japan Earthquake. The onset and progression of his symptoms were heavily affected by changes in his life after evacuation due to the postearthquake nuclear power plant accident. We were able to successfully implement structured CBT and help the patient better cope with his symptoms in a disaster-stricken location. CBT for PTSD includes exposure to traumatic memories, which may lead to worsening of PTSD symptoms, but we were able to administer the therapy successfully with clinical support through the use of modern information and communication technology.